African Buffalo Optimization Approach to the Design of PID Controller in Automatic Voltage Regulator System - Odili, Julius Beneoluchi; M. N. M., Kahar (Universiti Malaysia Pahang, 2016)
In the past few decades, researchers have focused so much attention on the application of bio-inspired techniques for solving real-life problems in science, engineering and industrial processes. This paper presents the African Buffalo Optimization (ABO) approach to tuning the Proportional, Integral and Derivative (PID) parameters of an Automatic Voltage Regulator. The ABO is a simulation of the movement of African Buffalos in the vast African landscape in search of lush grazing pastures using two basic sounds, namely the waaa and the maaa vocalizations. The ABO has so far been effective and efficient in providing solutions to a number of optimization problems as a result of its use of relatively fewer parameters, straightforward fitness function as well as regular communications using the star communication topology. Simulation results from the application of the ABO to tuning the parameters of an AVR has proven to be very competitive when compared with the results of other bio-inspired optimization techniques such as the GA-PID, ACO-PID, PSO-PID, BFO-PID, PID-PSO and PID Tuner.